International Financial Statistics, January 2017. (International Financial Statistics; Volume 70, January 2017, 2017)
This paper outlines the IMF's principal statistical publication, International Financial Statistics (IFS), has been published monthly since January 1948. In 1961, the monthly was supplemented by a yearbook, and in 1991 and 2000, respectively, IFS was introduced on CD-ROM and the Internet. IFS contains country tables for most IMF members, as well as for Anguilla, Aruba, the Central African Economic and Monetary Community (CEMAC), Curacao, the currency union of Curacao and Sint Maarten, the Eastern Caribbean Currency Union (ECCU), the euro area, Montserrat, the former Netherlands Antilles, Sint Maarten, the West African Economic Monetary Union (WAEMU), West Bank and Gaza, and some non-sovereign territorial entities for which statistics are provided internationally on a separate basis. Also, selected series are drawn from the country tables and published in area and world tables. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. Most annual data on the CD-ROM and Internet begin in 1948; quarterly and monthly data generally begin in 1957; most balance of payments data begin in 1970.